Formulation of Seaweed (Sargassum polycystum) and Mangrove (Rhizophora apiculata) Leaf as Antimosquito Lotion - Apriliani Endah Putri (EDP Sciences, 2021)
Mosquito repellent lotions generally use ingredients such as diethyltoluamide (DEET). DEET has been mixed by the manufacture of commercial mosquito repellent lotions and used by consumers without regard to the consequences if it is continuing used. Though many natural plants, especially marine plants can also provide the same benefits as a mosquito repellent. Therefore, in this study the aim was to make a lotion based on seaweed (Sargassum polycystum) and mangrove leaves (Rhizophora apiculata) as a mosquito repellent. The treatments in this study were 30% seaweed (L1), 30% mangrove leaf (L2), 15% seaweed, and 15% mangrove leaf (L3), and control (L0). The results showed that the effectiveness of the protective vover of anti-mosquito lotion S. polycystum (L1) was able to protect for 2 hours, (L2) mangrove leaf lotion was able to protect for 4 hours and S. polycycstum lotion and mangrove leaf R. apiculata (L3) were able to protect for 3 hours